Braving the Element: Pancreatic β-Cell Dysfunction and Adaptation in Response to Arsenic Exposure - Carmean, Christopher M.; Seino, Susumu (Frontiers in Endocrinology, 2019)
Type 2 diabetes mellitus (T2DM) is a serious global health problem, currently affecting an estimated 451 million people worldwide. T2DM is characterized by hyperglycemia and low insulin relative to the metabolic demand. The precise contributing factors for a given individual vary, but generally include a combination of insulin resistance and insufficient insulin secretion. Ultimately, the progression to diabetes occurs only after β-cells fail to meet the needs of the individual. The stresses placed upon β-cells in this context manifest as increased oxidative damage, local inflammation, and ER stress, often inciting a destructive spiral of β-cell death, increased metabolic stress due to further insufficiency, and additional β-cell death. Several pathways controlling insulin resistance and β-cell adaptation/survival are affected by a class of exogenous bioactive compounds deemed endocrine disrupting chemicals (EDCs). Epidemiological studies have shown that, in several regions throughout the world, exposure to the EDC inorganic arsenic (iAs) correlates significantly with T2DM. It has been proposed that a lifetime of exposure to iAs may exacerbate problems with both insulin sensitivity as well as β-cell function/survival, promoting the development of T2DM. This review focuses on the mechanisms of iAs action as they relate to known adaptive and maladaptive pathways in pancreatic β-cells.